Industrial minerals & rocks : commodities, markets, and uses. - Kogel, Jessica Elzea, 1959- (Society for Mining, Metallurgy, and Exploration, 2006)
This widely read global reference is one of the most authoritative sources for timely information on industrial minerals and rocks, the markets they serve, and their multitude of uses. Changes in the global economy have greatly impacted the mining, processing, and marketing of industrial minerals. Additionally, the development of new technologies and a globalization of the customer base have driven fast-paced innovation in processing, packaging, transporting, and end use. The new edition examines these important and diverse changes and their complex ramifications.